Fruit-Derived Anthocyanins: Effects on Cycling-Induced Responses and Cycling Performance - Cândice L. K. Copetti; Fernando Diefenthaeler; Fernanda Hansen; Francilene G. K. Vieira; Patricia F. Di Pietro (MDPI AG, 2022)
Previous evidence has shown that the consumption of fruit-derived anthocyanins may have exercise benefits. This review aimed to summarize the effects of fruit-derived anthocyanins on cycling-induced responses and cycling performance. Medline, Science Direct, Cochrane Library, and SPORTDiscus online databases were searched. Nineteen articles met the inclusion criteria. The fruit-derived anthocyanins used in these studies were from cherry (n = 6), blackcurrant (n = 8), pomegranate (n = 2), açai (n = 1), and juçara fruit (n = 2), and were offered in juice, pulp, powder, freeze-dried powder, and extract form. The supplementation time ranged from acute consumption to 20 days, and the amount of anthocyanins administered in the studies ranged from 18 to 552 mg/day. The studies addressed effects on oxidative stress (n = 5), inflammation (n = 4), muscle damage (n = 3), fatigue (n = 2), nitric oxide biomarkers (n = 2), vascular function (n = 2), muscle oxygenation (n = 2), performance (n = 14), substrate oxidation (n = 6), and cardiometabolic markers (n = 3). The potential ergogenic effect of anthocyanin supplementation on cycling-induced responses seems to be related to lower oxidative stress, inflammation, muscle damage, and fatigue, and increased production of nitric oxide, with subsequent improvements in vascular function and muscle oxygenation leading to improved performance. In addition, the observed increase in fat oxidation can direct nutritional strategies to change the use of substrate and improve performance.